Incisor inclination: estimate of the quantity of buccolingual displacement and their effects on the dental arc length - Tamayo-Lopera, Aicardo (Revista Facultad de Odontología Universidad de Antioquia, 2011)
Methods are presented to calculate more precisely the quantity of incisor displacement during buccolingual inclination movements. It is based on the arc length and chord length of a circle and law of sines with dynamic rotation center formulas. When preformed archwires are used during the orthodontic alignment phases, the inclination taking place on the anterior teeth affects the form and total arch length. At present this aspect has not been evaluated in depth. Guidelines are offered to calculate these variations with the purpose of achieving a more exact space analysis. Representations and case analysis reinforce this proposal.